Modal Ventura Indonesia - Myrna Sofia; Risdy Absari Indah Pratiwi; Firwan Tan; Nasri Bachtiar; Febriandi Prima Putra; Muhammad Hidayat (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
Venture capital companies (PMV) not only provide financial financing but also participate in providing strategic direction to investee (PPU), thus providing solutions for PPU in carrying out company operations. This study uses a quantitative descriptive method related to PMV conditions in Indonesia for the 2015-2020 period. As a result, the number of PMVs showed a decreasing trend, but in contrast to the number of PPUs, PMV performance, assets, liabilities and equity showed an increasing trend during the study period. This indicates that PMV in Indonesia is able to grow and develop even though the number of PMV has decreased. It is hoped that PMV can increase the financing of shares and convertible bonds, so that PMV is able to bring micro, small and medium companies to successfully exit and enter the expansion stage either through mergers, acquisitions or IPOs in the capital market.